(untitled) (Jurnal Sistem Informasi Akuntansi, 2023)
The operational system for bookings used by the Quantum Property company is still simple by utilizing Microsoft Office Excel in the unit booking process. This certainly has an impact on the slow process of processing data on the business processes that are carried out. After knowing the running system and the problems experienced by Quantum Property, the purpose of this research is to create a website-based payment information system and management of house unit bookings. The results of this system design can be used by home booking providers as a basic reference for taking solutions to existing problems and good and effective management. The research method used is descriptive research method which aims to describe, explain and describe certain phenomena related to the research object. With this website-based information system, the availability of complete property information is more easily accessed by potential customers so that they can see the specifications of what houses are being sold by Quantum Property.